Granular Cell Tumor: A Technical Approach for Resection of a Rare Suprasellar Mass. Issue 4 (28th November 2020) - Schupper, Alexander J; Yuk, Frank J; Zou, Hongyan; Ahuja, Sadhna; Tsankova, Nadejda M; Hadjipanayis, Constantinos G
Abstract: BACKGROUND AND IMPORTANCE: Granular cell tumors (GCTs) of the sellar and suprasellar regions are rare tumors that may be managed surgically by multiple strategies. The technical approaches for these tumors have rarely been described in the literature. CLINICAL PRESENTATION: We introduce the case of a patient presenting with dizziness and headaches who was found to have a suprasellar and retrochiasmatic mass and eventually underwent surgical resection. We discuss the characteristics of this tumor, and the current state of the literature. Also included are details regarding the surgical approach utilized in this case, and a discussion of the various surgical approaches for this type of tumor. CONCLUSION: There are several approaches for the surgical resection of suprasellar GCTs, and the approach utilized may depend on patient and/or surgeon considerations. Patient-specific considerations must be made to ensure maximal safe resection of these lesions.